The 100 most-cited articles in urological surgery: A bibliometric analysis. (March 2020) - He, Lugeng; Fang, Hui; Wang, Xuliang; Wang, Yuyong; Ge, Hongwei; Li, Changjiu; Chen, Chao; Wan, Yuehua; He, Huadong
Abstract: Background: The purpose of this bibliometric analysis was to identify and assess the 100 most-cited articles (T100 articles) on urological surgery. Methods: The Web of Science (WoS) Core Collection database was used to investigate the T100 articles in the field of urological surgery. Different aspects of the T100 articles, including the countries, journals, authors, and topics, were analyzed. Results: The number of citations of T100 articles published between 1989 and 2016 ranged from 334 to 2189. The T100 articles originated from 28 countries, with more than half originating from the USA (n = 80). Professor Bill-Axelson A from Uppsala University Hospital published the largest number of T100 articles as the first author (4) and as a coauthor (1). The Memorial Sloan Kettering Cancer Center from the USA is the top institution with the most T100 articles in the field of urological surgery. The special journal Journal of Urology published 41 of the T100 articles, which had a total of 19780 citations. Conclusions: Our study analyzed the 100 most-cited articles in the field of urological surgery. The USA is the dominant country in terms of the number of T100 articles, scientists and institutions. Surgery related to urological cancer has garnered the most academic attention, especially prostate cancer and renal cancer. Highlights: A bibliometric analysis was performed, establishing the most influential publications in the field of urological surgery. The USA is the dominant country in terms of the number of T100 articles, scientists and institutions. Surgery related to urological cancer has garnered the most academic attention, especially prostate cancer and renal cancer.